Strengthening Pancasila Values Through Youth Flag-Raising Troops: A Community-Based Program in Ciomas, Bogor - Elistiana; Purwanto; Upa, Fatmawati Pua (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to strengthen the values of Pancasila among members of the Paskibra team in Ciomas Sub-district, Bogor Regency. The selected high school students, after passing the selection process, participated in a weekly training program that focused on ideological, leadership, and national character education. This was followed by an intensive training phase conducted seven days before the Indonesian Independence Day celebration on August 17th. The method used was Community-Based Research (CBR), involving collaboration between academics, community leaders, and local government. Training materials were based on national guidelines issued by the Agency for the Implementation of Pancasila Ideology Development (BPIP) and were adapted to the local context. The results showed increased understanding and internalization of Pancasila values such as nationalism, discipline, cooperation, and leadership among the participants. The activity not only improved their performance in ceremonial duties but also shaped their character as future leaders. This program demonstrates the effectiveness of integrating national ideology education into youth leadership activities.